Control of ZnO crystallization by a PEO-b-PMAA diblock copolymer - Oner, M; Norwig, J; Meyer, WH; Wegner, G (AMER CHEMICAL SOC, 1998)
Amphipolar diblock copolymers used as admixtures provide a unique effect on crystallization processes from solution. In an example given here, nucleation of ZnO crystals and growth of specific crystal faces is controlled by minute amounts of PEO-b-PMAA copolymers. A narrow crystal size distribution and retardation of growth parallel to [001] are observed in dependence on the concentration of the block copolymer, which is added in the ppm range.
Keywords: CRYSTAL-GROWTH; ZINC-OXIDE; INHIBITION; POLYELECTROLYTES; PRECIPITATION; AGGREGATION; SURFACES; COLLOIDS; METAL; Chemistry; Materials Science